Diversity at Work: Working With and Managing Diversity - Dickie, Carolyn; Soldan, Zhanna; Fazey, M. (Tilde Publishing Australia, 2011)
Synopsis: The ‘diversity’ concept provides an essential means of developing an inclusive, competitive workplace in a comprehensive and encompassing manner. The aim of this book is to familiarise students with the theory and practice of diversity and diversity management at work. It provides clarity and focus to the areas of diversity and diversity training, and outlines the nature of diversity understanding and research for the benefit of employees, managers, educators and training professionals. This book can also be an experiential learning tool for people interested in 21st century business. It has theoretical, conceptual and practical content – as well as numerous discussion points and examples – which will challenge current and future business leaders.